(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2018)
The following writing is under the frame of the project of investigation: political ‘Subjectivity and educational memories: between the political violence and the school’ in the frame of the Interinstitutional Doctorate in Education DIE Universidad Distrital Francisco José de Caldas, emphasis in History of the Education, Pedagogy and Compared Education, line of investigation: Political Formation and Social Memory and despliega the different works that national and international have developed in the last decades on the relation that is emerged between the memories that the teachers enunciate on their histories of life and the crossing of these with situations of the armed conflict and the political violence in diverse contexts of life and development of his work educational. In sum, one presents the production of investigations, books, thesis and research reports that realize of the relation teachers’ memories, history of life, armed conflict, political violence and school.